2020
DOI: 10.1038/s41598-020-64971-9
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear compositional and morphological evolution of ion irradiated GaSb prior to nanostructure formation

Abstract: Low-energy ion irradiation of III-V semiconductor surfaces can lead to the formation of regular hexagonal dot patterns at the surface. We present experimental and computational results for ion irradiation of GaSb surfaces which elucidate the nature of the coupled compositional and morphological pattern-formation mechanisms. We demonstrate by in-situ grazing-incidence small-angle x-ray scattering (GISAXS) and angle-resolved Auger electron spectroscopy (ARAES) that the emergence of an altered compositional depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
(43 reference statements)
0
1
0
Order By: Relevance
“…In addition, by means of atomistic simulations, the authors suggested that ion-enhanced mobility associated with energy deposition by collision cascades could be the microscopic mechanism of this process [15]. Recently, this mobility issue on IBI GaSb patterning was addressed through experimental (GISAXS and angle-resolved Auger electron spectroscopy) and molecular dynamics simulations [181]. In this work, the simulations showed that, on the irradiated surface, Sb may be more mobile than Ga.…”
Section: Ibi Patterning Of Compound Surfacesmentioning
confidence: 83%
“…In addition, by means of atomistic simulations, the authors suggested that ion-enhanced mobility associated with energy deposition by collision cascades could be the microscopic mechanism of this process [15]. Recently, this mobility issue on IBI GaSb patterning was addressed through experimental (GISAXS and angle-resolved Auger electron spectroscopy) and molecular dynamics simulations [181]. In this work, the simulations showed that, on the irradiated surface, Sb may be more mobile than Ga.…”
Section: Ibi Patterning Of Compound Surfacesmentioning
confidence: 83%